A equidade do orçamento estadual do RS-2011 - Brunet, Júlio Francisco Gregory (2013)
Propose a methodology for analyzing equity in revenue and total expenditure public resources of state budgets on a regional scale including tax exemptions is the aim of this work. The object of analysis is the Budget State of Rio Grande do Sul in 2011. Although the fact of federal government has the main responsibility to correct vertical and horizontal imbalances between the local governments, the influence of state´s budge, considering its proportion in local economies, cannot be neglected, The work is structured in four chapters. A literature review abording the discussion of equity on national and regional levels is contemplated on chapter 2. In Chapter 3, the methodology used to obtain the regionalization of the State budget, both for revenue and for expenses, including Tax Expenditures is detailed. For the results evaluation, the main components of revenues and expenses were unfolded by region and per capita. The reference for comparison is the average income of the State. And so the both sides of the equation budget, revenues and expenses, and, balance, tested to analyze equity. The budget balance resulting from this, show us the less or greater progressivity, of the budget in the regions. In Chapter 4 will also be examined the proportion of servers in regions depending on income per capita, as well as a comparison with the HDI. In Chapter 5 will be the general conclusions of the work. Briefly, it was concluded that although the exaction is neutral on the income of the regions and the expenditure not present mechanisms that enhance equity, on balance, i.e. the budget balance resulting from the exaction and expense signs relative progressivity of the income regions, benefiting, albeit inhomogeneous the poorest regions of the state. The inhomogeneity of the distribution of the balance budget in regions points where concentrate efforts to improve the budgetary income of the poorest regions.